CLINICOPATHOLOGICAL FEATURES OF CHILDHOOD VISCERAL LEISHMANIASIS IN AZAD JAMMU & KASHMIR PAKISTAN - Altaf, Chauhdry; Ahmed, Parvez; Ashraf, Tanveer; Anwar, Masood; Ahmed, Irfan (Journal of Ayub Medical College Abbottabad, 2005)
Background: In Pakistan visceral leishmaniasis (VL) is endemic in Azad Jammu & Kashmir, Northern Areas and Northwest Frontier Province; the areas which lack adequate diagnostic facilities. This study describes the clinical and laboratory features in 61 cases of childhood VL. Methods: All the children below 12 years of age who were managed as indoor cases from 1st Jan 1999 to 31st Dec 1999 were included in this study. The diagnosis of VL was established by demonstration of leishmania parasites in bone marrow aspiration. The demographic information, physical signs at presentations and results of complete blood picture and formol gel test were recorded. Results: Median age of the patients was 18 months. Eighty four percent children were malnourished. Mean duration of fever before diagnosis was 45 days. Hepatosplenomegaly was present in all cases with mean enlargement of spleen and liver 6.8 and 3.2 cm respectively. Mean haemoglobin level, WBC and platelet counts were 6.7 g/dl, 4.8 x 109 /l and 70 x 109 /l respectively. Absolute neutrophil count was <1.5 x 109 /l in 61% cases. Mean reticulocyte count was 6.2%. There was significant negative correlation (p= 0.014) between haemoglobin level and spleen size. Formol gel test was positive in all cases. Mean hospital stay to established diagnosis was 8.6 days. Conclusion: The clinical and laboratory features of childhood VL in Azad Jammu and Kashmir are similar to Mediterranean type of disease caused by leishmania infantum. Cytopenia with high or normal reticulocyte count provides a useful clue to diagnosis in a febrile patient with hepatosplenomegally in an endemic area. Key words: leishmaniasis, visceral childhood, clinicopathological